1994
DOI: 10.1111/j.1365-3059.1994.tb00565.x
|View full text |Cite
|
Sign up to set email alerts
|

Interactions between Erysiphe graminis and Septoria nodorum on wheat

Abstract: Interactions between Erysiphe graminis f.sp. tritici and Septoria nodorum on wheat were studied in the greenhouse and in a 2‐year field experiment using artificial inoculation. The integrated form of the logistic growth model dy/dt = ry (1 ‐y/K), with infection rate r and final accumulated disease K, was fitted to the disease progress data. Septoria nodorum substantially reduced the disease severities of E. graminis, and caused significant reductions of at least 60% in final accumulated disease K of E. gramini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0

Year Published

1996
1996
2014
2014

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 12 publications
0
18
0
Order By: Relevance
“…M. graminicola acted as a hypostatic parasite. Weber et al (1994) observed that, in greenhouse, S. nodorum reduced the severity of mildew. On the other hand, under field conditions, E. graminis increased the final intensity of S. nodorum.…”
Section: Not Clearmentioning
confidence: 98%
See 4 more Smart Citations
“…M. graminicola acted as a hypostatic parasite. Weber et al (1994) observed that, in greenhouse, S. nodorum reduced the severity of mildew. On the other hand, under field conditions, E. graminis increased the final intensity of S. nodorum.…”
Section: Not Clearmentioning
confidence: 98%
“…However, even for wheat, the crop that receives the most attention regarding interactions among diseases, there are little multi-disease studies concerning management or epidemiological approaches. Moreover, the observed effects of reported interactions (for instance synergism, antagonism or additive effect) are highly dependent on inoculum concentration, disease levels (Jörg, 1987;Weber et al, 1994), pre-infection by one of the interacting pathogens (Donchev et al, 1980), and climatic conditions (Weber et al, 1994). Cox et al (2004) have demonstrated the potential of cultivar mixtures for the simultaneous management of tan spot (Pyrenophora tritici-repentis) and leaf rust of wheat (Puccinia triticina).…”
Section: Not Clearmentioning
confidence: 99%
See 3 more Smart Citations